Microsolvation of molecules in superfluid helium nanodroplets revealed by means of electronic spectroscopy - Premke, Tobias; Wirths, Eva-Maria; Pentlehner, Dominik; Riechers, Ricarda; Lehnig, Rudolf; Vdovin, Alexander; Slenczka, Alkwin (Frontiers in Chemistry, 2014)
The empirical model explaining microsolvation of molecules in superfluid helium droplets proposes a non-superfluid helium solvation layer enclosing the dopant molecule. This model warrants an empirical explanation of any helium induced substructure resolved for electronic transitions of molecules in helium droplets. Despite a wealth of such experimental data, quantitative modeling of spectra is still in its infancy. The theoretical treatment of such many-particle systems dissolved into a quantum fluid is a challenge. Moreover, the success of theoretical activities relies also on the accuracy and self-critical communication of experimental data. This will be elucidated by a critical resume of our own experimental work done within the last ten years. We come to the conclusion that spectroscopic data and among others in particular the spectral resolution depend strongly on experimental conditions. Moreover, despite the fact that none of the helium induced fine structure speaks against the empirical model for solvation in helium droplets, in many cases an unequivocal assignment of the spectroscopic details is not possible. This ambiguity needs to be considered and a careful and critical communication of experimental results is essential in order to promote success in quantitatively understanding microsolvation in superfluid helium nanodroplets.